2013
DOI: 10.1089/pho.2012.3433
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Follow-Up Findings in Imaging Manifestation After Percutaneous Laser Disc Decompression

Abstract: PLDD did not obviously lower the height of the intervertebral space, instead, it could effectively promote the reduction of disc herniation. By analyzing the medical images, we found that PLDD is a safe and effective minimal invasive surgery for cervical and lumbar disc diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…The result would be a decline in intradiscal pressure and also a more even distribution of weight across the disc, with a subsequent relief of discogenic pain; this is performed most commonly for lumbar disc pathologies [16,17]. Due to its minimally-invasive nature, the decrease in the risk of damage to the muscles, bone, ligaments, and nerves along with less back pain, a shorter hospital stay and shorter recovery period in comparison with conventional surgical methods are anticipated, and several cohort studies have previously showed the safety and potential benefits of PLDD [7,8,16,[18][19][20][21][22][23]. On the other hand, multiple prospective randomized trials do exist that have revealed the lack of efficacy of PLDD alone or compared with conventional surgeries such as microdiscectomy [9,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…The result would be a decline in intradiscal pressure and also a more even distribution of weight across the disc, with a subsequent relief of discogenic pain; this is performed most commonly for lumbar disc pathologies [16,17]. Due to its minimally-invasive nature, the decrease in the risk of damage to the muscles, bone, ligaments, and nerves along with less back pain, a shorter hospital stay and shorter recovery period in comparison with conventional surgical methods are anticipated, and several cohort studies have previously showed the safety and potential benefits of PLDD [7,8,16,[18][19][20][21][22][23]. On the other hand, multiple prospective randomized trials do exist that have revealed the lack of efficacy of PLDD alone or compared with conventional surgeries such as microdiscectomy [9,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Açıkça PLDD intervertebral disk yüksekliğini daha fazla azaltmaz bunun yerine disk herniasyonunun azalmasını etkin bir şekilde düzenlediği gösterilmiştir (29) . Medikal görüntülerin analizi sonucundaki bulguların, PLDD'nin lumbal ve servikal disk hernileri için etkin ve güvenlir olduğu şeklindedir (29) .…”
Section: Spinal Instabilite Ağrısıunclassified
“…[162027] Ren et al . (2013) found no alternation of disc height before and after cervical and lumbar PLDD (all 22 patients with “contained” discs) [Table 3].…”
Section: Introductionmentioning
confidence: 99%
“…(2013) found no alternation of disc height before and after cervical and lumbar PLDD (all 22 patients with “contained” discs) [Table 3]. [20] Lee and Lee (2014) documented 37 patients undergoing percutaneous cervical laser disc ablations (no control group); all improved (e.g., using the neck disability index (NDI)) [Table 3]. [16] Yang et al .…”
Section: Introductionmentioning
confidence: 99%